Proccedings of 10th International Conference "Environmental Engineering" 2017
DOI: 10.3846/enviro.2017.255
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Outside Temperature on the Operation of the Adsorption Chiller

Abstract: Abstract. Adsorption refrigeration systems are characterized by a lower coefficient of performance than the compressor type device or even absorption, but can utilize waste heat at lower temperature. The aim of the study was to determine which external parameter has the greatest impact on the efficiency of the adsorption device. As a result of experimental studies there was found that this is not the temperature of the feed but particularly the temperature of external air. For this reason, it is recommended th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…The efficiency and capacity of thermal energy-driven systems are highly dependent on the outdoor temperature more than VC systems. Therefore, they are not strongly resilient to heatwaves, while for sorption systems, a previous study has shown that using a spray-evaporative heat exchanger can reduce the effect of the outdoor temperature on the sorption system capacity [108].…”
Section: Findings and Recommendationsmentioning
confidence: 99%
“…The efficiency and capacity of thermal energy-driven systems are highly dependent on the outdoor temperature more than VC systems. Therefore, they are not strongly resilient to heatwaves, while for sorption systems, a previous study has shown that using a spray-evaporative heat exchanger can reduce the effect of the outdoor temperature on the sorption system capacity [108].…”
Section: Findings and Recommendationsmentioning
confidence: 99%